Long‐term climate and competition explain forest mortality patterns under extreme drought. (January 2017) - Young, Derek J. N.; Stevens, Jens T.; Earles, J. Mason; Moore, Jeffrey; Ellis, Adam; Jirka, Amy L.; Latimer, Andrew M.
Abstract: Rising temperatures are amplifying drought‐induced stress and mortality in forests globally. It remains uncertain, however, whether tree mortality across drought‐stricken landscapes will be concentrated in particular climatic and competitive environments. We investigated the effects of long‐term average climate [i.e. 35‐year mean annual climatic water deficit (CWD)] and competition (i.e. tree basal area) on tree mortality patterns, using extensive aerial mortality surveys conducted throughout the forests of California during a 4‐year statewide extreme drought lasting from 2012 to 2015. During this period, tree mortality increased by an order of magnitude, typically from tens to hundreds of dead trees per km 2, rising dramatically during the fourth year of drought. Mortality rates increased independently with average CWD and with basal area, and they increased disproportionately in areas that were both dry and dense. These results can assist forest managers and policy‐makers in identifying the most drought‐vulnerable forests across broad geographic areas.